The Predictive Nature of Pseudoneglect for Visual Neglect: Evidence from Parietal Theta Burst Stimulation. - Alice Varnava; Martynas Dervinis; Christopher D Chambers (PLoS ONE)
Following parietal damage most patients with visual neglect bisect horizontal lines significantly away from the true centre. Neurologically intact individuals also misbisect lines; a phenomenon referred to as 'pseudoneglect'. In this study we examined the relationship between neglect and pseudoneglect by testing how patterns of pre-existing visuospatial asymmetry predict asymmetry caused by parietal interference. Twenty-four participants completed line bisection and Landmark tasks before receiving continuous theta burst stimulation to the left or right angular gyrus. Results showed that a pre-existing pattern of left pseudoneglect (i.e. right bias), but not right pseudoneglect, predicts left neglect-like behaviour during line bisection following right parietal cTBS. This correlation is consistent with the view that neglect and pseudoneglect arise via a common or linked neural mechanism.